Preparation method of titanium oxycarbide electrode, titanium oxycarbide electrode and application of titanium oxycarbide electrode

By adding asphalt and binder to the preparation process of carbon titanium oxide electrodes for sintering, the problems of low electrode dissolution rate and frequent replacement are solved, and efficient titanium refining is achieved and production costs are reduced.

CN119615299APending Publication Date: 2025-03-14PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411926467.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing carbon titanium oxide electrodes have low dissolution rate and frequent electrode peeling and replacement during the electrolysis process, resulting in high production costs and low efficiency.

Method used

By mixing the carbon reducing agent, titanium-containing material and binder for carbon thermal reduction treatment, obtaining the reduction product, adding bitumen and binder for sintering, and preparing a carbon titanium oxide electrode with high dissolution properties.

Benefits of technology

It improves the dissolution rate of the anode electrode, extends the service life of the electrode, reduces energy consumption and electrode preparation cost, and the anode dissolution rate can reach more than 90%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a titanium oxycarbide electrode, the titanium oxycarbide electrode and application of the titanium oxycarbide electrode. The preparation method comprises the following steps: mixing a carbon reducing agent, a titanium-containing material and a binder, carrying out carbon thermal reduction treatment to obtain a reduction product, introducing asphalt and the binder, and sintering to obtain the carbon titanium oxide electrode. Wherein the addition of the asphalt can play an excellent role of a pore-forming agent, so that the prepared titanium oxycarbide electrode has higher solubility, the anode dissolution rate in a low-valence titanium system can reach 90% or above, the density of the secondarily formed titanium oxycarbide electrode is greatly increased, and the content of the titanium oxycarbide is increased by 60% or above; the problems of low dissolution rate, electrode stripping, frequent electrode replacement and the like of the titanium oxycarbide anode in the electrolysis process in the prior art are solved, and the energy consumption and the electrode preparation cost are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare metal refining, and specifically relates to a preparation method of a titanium oxycarbide electrode, a titanium oxycarbide electrode and applications thereof. Background Art

[0002] As a metal with very superior properties, titanium has a series of advantages such as light specific gravity, high specific strength, and good corrosion resistance. It has been increasingly widely used in various industries such as national defense, chemical industry, metallurgy, medical treatment, industrial and agricultural production, especially in the field of high technology.

[0003] At present, the production method of titanium metal is magnesium reduction method (Kroll process), and the whole production process includes four main parts: chlorination of titanium oxide, thermal reduction of magnesium, vacuum distillation and electrolysis of magnesium chloride. Due to the shortcomings of long production process, long cycle, high energy consumption and intermittent production, the production cost of titanium sponge is too high. At present, the Kroll process is quite mature and there is little room for improvement.

[0004] The USTB method (CN1712571A) was proposed by the University of Science and Technology Beijing as a method for producing pure titanium by anodic electrolysis of a soluble solid solution of titanium monoxide / titanium carbide. This method uses a carbonaceous reducing agent and a titanium-containing material as raw materials, and obtains a titanium oxide solid solution TiC after pressing and high-temperature vacuum reduction. x O y , crushed, re-molded and sintered into electrodes, and electrolyzed in a chloride molten salt system containing low-valent titanium ions. During the electrolysis process, the solid solution TiC x O y The titanium in the electrolyte enters the molten salt in the form of ions, and the remaining carbon and oxygen overflow the electrolysis system in the form of CO. In theory, no residual carbon will be produced at the anode, and pure metallic titanium will be deposited on the cathode. However, the anode electrode of this method has the following problems: (1) The prepared electrode has the problem of uneven distribution of microstructural elements. During the electrolysis process, amorphous carbon will be generated and attached to the electrode surface, hindering the diffusion of ions during the electrolysis process, resulting in reduced electrode dissolution efficiency and current efficiency; (2) The gas generated on the anode surface during the electrolysis process will scour the electrode surface, causing the surface of the anode material to peel off into fine particles and sink to the bottom of the electrolytic cell, thereby reducing the utilization rate of the anode; (3) The preparation of titanium oxycarbon electrode requires a high-temperature reduction, crushing, molding, secondary sintering and other processing steps, resulting in a high cost for the preparation of the electrode.

[0005] Based on the above problems, patent CN 115652372 A proposed a coating method for preparing titanium oxycarbide electrodes, which introduces a binder and a pore-forming agent into the raw materials to make the prepared electrodes less likely to peel off. Although this method has made some improvements over the USTB method for electrode preparation, it still has problems such as low anode dissolution rate and low titanium oxycarbide content in the electrode, which leads to frequent electrode replacement. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a method for preparing a titanium oxycarbide electrode, a titanium oxycarbide electrode and its application. The preparation method can improve the dissolution rate of the anode electrode and reduce the frequency of electrode replacement.

[0007] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a titanium oxycarbide electrode, comprising the following steps: S1: mixing a carbon reducing agent, a titanium-containing material and a binder, and then performing a carbon thermal reduction treatment to obtain a reduction product; S2: The reduction product is mixed with asphalt and a binder, and then sintered to obtain a titanium oxycarbide electrode.

[0008] Preferably, the fixed carbon content of the asphalt is 5-95 wt%.

[0009] Preferably, the particle size of the asphalt is 40-5000 μm.

[0010] Preferably, the carbon reducing agent is selected from any one or more of graphite, petroleum coke or amorphous carbon. In the present invention, the higher the purity of the carbon reducing agent, the better.

[0011] Preferably, the titanium-containing material is selected from any one or more of titanium dioxide, rutile, artificial rutile, titanium concentrate, titanium slag or high-titanium slag.

[0012] Preferably, the binder in steps S1 and S2 is independently selected from water and / or an aqueous solution of polyvinyl alcohol.

[0013] Preferably, the mass fraction of polyvinyl alcohol in the aqueous solution of polyvinyl alcohol is 1-2%.

[0014] Preferably, the molar ratio of carbon in the carbon reducing agent to titanium dioxide in the titanium-containing material is 1.6:1 to 2.4:1.

[0015] Preferably, the water content in the mixture of the carbon reducing agent, the titanium-containing material and the binder is 12-15%.

[0016] Preferably, the mass of the asphalt accounts for 10-30% of the total mass of the asphalt and the titanium oxycarbide electrode.

[0017] Preferably, the mass of the binder in step S2 accounts for 5-7% of the total mass of the reduction product and asphalt.

[0018] Preferably, the temperature of the carbon thermal reduction treatment is 1280-1800° C., the time is 0.5-10 h, and the pressure is ≤1 atm.

[0019] Preferably, the heating rate in the carbothermal reduction treatment is 5-15°C / min.

[0020] Preferably, the carbothermal reduction treatment is performed in an inert atmosphere or a vacuum environment.

[0021] Preferably, the sintering is performed in an inert atmosphere.

[0022] Preferably, the sintering is carried out according to the following procedure: Raise the temperature to 300-400°C at a rate of 5-15°C / min and keep at this temperature for 1-5 h; Raise the temperature to 450-550°C at a rate of 5-15°C / min and keep at this temperature for 1-5 h; Raise the temperature to 850~1050℃ at a rate of 5~15℃ / min and keep it at this temperature for 1~5 h.

[0023] Preferably, after the mixing in step S1, compression molding is performed, and then a carbon thermal reduction treatment is performed; the compression molding pressure is 25-600 MPa.

[0024] Preferably, the reduction product in step S2 is crushed and sieved in advance, and the mesh number of the sieve is 20-100 meshes.

[0025] Preferably, after the mixing in step S2, compression molding is performed, and then sintering is performed; the compression molding pressure is 5-80 MPa.

[0026] In a second aspect, the present invention also provides a titanium oxycarbide electrode prepared by the above preparation method, wherein the density is preferably 1.5 g / cm 3 above.

[0027] In a third aspect, the present invention also provides an application of the titanium oxycarbide electrode involved in the above technical solution in titanium extraction by molten salt electrolysis.

[0028] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a titanium oxycarbide electrode, which firstly mixes a carbon reducing agent, a titanium-containing material, and a binder, performs a carbon thermal reduction treatment, and after obtaining a reduction product, introduces asphalt and a binder, performs sintering, and obtains a titanium oxycarbide electrode. The addition of asphalt can play the role of an excellent pore-forming agent, so that the prepared titanium oxycarbide electrode has higher solubility performance, and the anode dissolution rate in a low-valent titanium system can reach more than 90%. After secondary molding, the density of the titanium oxycarbide electrode is greatly increased, and the titanium oxycarbide content is increased by more than 60%, which solves the problems of low dissolution rate of the titanium oxycarbide anode during electrolysis, electrode peeling, and frequent electrode replacement in the prior art, and reduces energy consumption and electrode preparation costs. At the same time, the asphalt is added after the carbon thermal reduction treatment and does not participate in the carbon thermal reduction reaction, thereby avoiding the reduction of electrode strength caused by the large amount of asphalt added. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In order to further improve the dissolution rate of titanium oxycarbide electrodes and solve the problem of frequent electrode replacement, the present invention provides a method for preparing porous titanium oxycarbide electrodes using carbon reducing agents, asphalt, titanium-containing materials, etc. as raw materials. Compared with traditional methods for preparing titanium oxycarbide electrodes, the method has the advantages of low energy consumption, high titanium oxycarbide content, high electrode utilization rate and not easy to peel off during electrolysis.

[0031] Specifically, the method for preparing a porous titanium oxycarbide electrode of the present invention comprises the following steps: S1: mixing a carbon reducing agent, a titanium-containing material, and a binder in a certain proportion, performing compression molding, and performing carbon thermal reduction treatment after drying to obtain a reduction product; S2: The reduction product is crushed and sieved, mixed with asphalt and a binder in a certain proportion, molded, dried and sintered to obtain a titanium oxycarbide electrode.

[0032] In the present invention, the carbon reducing agent is selected from any one or more of graphite, petroleum coke or amorphous carbon. In the present invention, the higher the purity of the carbon reducing agent, the better.

[0033] In the present invention, the titanium-containing material is selected from any one or more of titanium dioxide, rutile, artificial rutile, titanium concentrate, titanium slag or high-titanium slag, preferably titanium dioxide. When the titanium-containing material is selected from a material other than titanium dioxide, it generally needs to be pre-treated to remove impurities.

[0034] In the present invention, the binder in steps S1 and S2 is independently selected from water and / or an aqueous solution of polyvinyl alcohol; the mass fraction of polyvinyl alcohol in the aqueous solution of polyvinyl alcohol is 1-2%, specifically 1%, 1.5%, or 2.0%.

[0035] In some embodiments of the present invention, it is preferred to use water as the binder in step S1 and to use an aqueous solution of polyvinyl alcohol as the binder in step S2.

[0036] According to the present invention, a carbon reducing agent, a titanium-containing material, and a binder are mixed in a certain ratio to obtain a mixture, wherein the molar ratio of carbon in the carbon reducing agent to titanium dioxide in the titanium-containing material is 1.6:1-2.4:1, preferably 1.9:1-2.1:1; and the water content of the mixture of the carbon reducing agent, the titanium-containing material, and the binder is 12-15%, preferably 13-14%.

[0037] After obtaining the mixture, it is subjected to compression molding, and the compression molding pressure is 25-600 MPa, preferably 50-500 MPa, and more preferably 200-300 MPa. The compression molding is carried out in a mold according to means well known to those skilled in the art. Then, a drying treatment is carried out. The temperature of the drying treatment is 100-120° C., preferably 105-110° C.; the drying treatment time is generally more than 10 h, preferably more than 12 h.

[0038] After drying, the obtained product is subjected to carbon thermal reduction treatment in an inert atmosphere or a vacuum environment. The present invention has no particular limitation on the inert atmosphere, and any atmosphere familiar to those skilled in the art can be used.

[0039] In some embodiments of the present invention, the product is subjected to a carbothermal reduction treatment in a vacuum furnace, during which C combines with O in TiO2 and is released in the form of CO. The carbothermal reduction treatment is preferably carried out at a rate of 5 to 15 °C / min, more preferably 10 °C / min, to a temperature of 1280 to 1800 °C, preferably 1350 to 1550 °C; for a time of 0.5 to 10 h, preferably 3 to 6 h; and at a pressure of ≤1 atm, preferably ≤300 Pa.

[0040] In the present invention, after the carbon thermal reduction treatment is completed, the product is cooled out of the furnace and the reduction product is crushed to 20-100 meshes, preferably 40-60 meshes.

[0041] Then, according to the present invention, the sieved product is mixed with asphalt and a binder in a certain proportion, molded, dried and sintered. It should be noted that if the proportion of asphalt is too high, although the number of pores will be more, the strength of the prepared electrode will decrease, which will cause shedding during electrolysis and physical loss during loading and unloading; conversely, if the proportion of asphalt is too low, although the electrode strength is high, the number of pores will decrease, which will cause a decrease in solubility. Therefore, in some embodiments of the present invention, the mass of the asphalt accounts for 10-30% of the total mass of the asphalt and the titanium oxycarbide electrode, preferably 15-25%.

[0042] In the present invention, asphalt is used as a pore-forming agent. In an inert atmosphere, the volatile components therein will volatilize, leaving fixed carbon, thereby achieving the purpose of pore formation. Among them, the fixed carbon content of the asphalt has an impact on the number of pores. Therefore, after screening, the present invention preferably has a fixed carbon content of 5 to 95 wt%, more preferably 30 to 70 wt%, and further preferably 40 to 60 wt%.

[0043] In the present invention, the particle size of the asphalt has an impact on the size of the pores formed subsequently. Therefore, after screening, the present invention preferably has a particle size of 40 to 5000 μm, and more preferably 100 to 2000 μm.

[0044] In the present invention, the mass of the binder in step S2 accounts for 5-7% of the total mass of the reduction product and the asphalt, preferably 5.5-6.5%.

[0045] In the present invention, after the above-mentioned sieved product is mixed with asphalt and a binder, the obtained product is molded, and the pressure of the molding is 5~80 MPa, preferably 15~60 MPa. The molding is carried out in a mold according to means well known to those skilled in the art. Then, it is dried, and the drying temperature is 25°C~the melting point of asphalt, and the time is generally more than 10 hours, preferably more than 12 hours. In some embodiments of the present invention, it is preferably dried at 100°C for more than 12 hours.

[0046] After drying, sintering is performed. The sintering is preferably performed in an inert atmosphere. In some embodiments of the present invention, Ar gas is preferably introduced into an atmosphere furnace for sintering. The sintering is performed according to the following procedure: Raise the temperature to 300-400°C at a rate of 5-15°C / min and keep at this temperature for 1-5 h; Raise the temperature to 450-550°C at a rate of 5-15°C / min and keep at this temperature for 1-5 h; Raise the temperature to 850~1050℃ at a rate of 5~15℃ / min and keep it at this temperature for 1~5 h.

[0047] Preferably, the sintering is carried out according to the following procedure: Raise the temperature to 330-350℃ at a rate of 8-12℃ / min and keep at this temperature for 1-3 hours; Raise the temperature to 480-500°C at a rate of 8-12°C / min and keep at this temperature for 1-3 h; Raise the temperature to 900~1000℃ at a rate of 8~12℃ / min and keep it at this temperature for 1~3 h.

[0048] More preferably, the sintering is carried out according to the following procedure: Raise the temperature to 350°C at a rate of 10°C / min and keep at this temperature for 1 h; Raise the temperature to 500°C at a rate of 10°C / min and keep at this temperature for 1 h; The temperature was raised to 950°C at a rate of 10°C / min and kept at this temperature for 1 h.

[0049] After sintering, according to the present invention, the titanium electrode can be carbonized after cooling out of the furnace.

[0050] In the present invention, the density of the titanium oxycarbide electrode obtained according to the above preparation method is 1.5 g / cm 3 above.

[0051] The present invention also provides an application of the above-mentioned titanium oxycarbide electrode in titanium extraction by molten salt electrolysis.

[0052] Specifically, a titanium oxide carbon electrode is used as the anode, and electrolysis is carried out in a low-valent titanium electrolyte mainly composed of trivalent titanium ions. After the electrolysis is completed, the shape of the residual anode remains intact, forming a carbon skeleton, and the anode dissolution rate is high, reaching more than 90%.

[0053] In summary, the method for preparing the titanium oxycarbide electrode proposed in the present invention optimizes the addition method of asphalt so that asphalt does not serve as a reactant for carbon thermal reduction, retains its role as a pore-forming agent and carbonaceous skeleton, improves the dissolution rate of the electrode, and the content of titanium oxycarbide after electrode formation, and reduces the frequency of electrode replacement. At the same time, the prepared titanium oxycarbide electrode avoids the peeling of the anode under gas scouring during the electrolysis process, eliminates the high-temperature secondary forming link, reduces energy consumption, and can reduce the cost of electrode preparation by more than 30%. In addition, due to its loose and porous nature, it has a relatively high solubility performance, and the anode dissolution rate is increased from 50% to more than 90%, which provides a basis for the development of new extraction technologies for metallic titanium.

[0054] It has been verified that this method has been applied to the new titanium metal extraction technology currently under development, achieving a balance between anodic dissolution and cathodic precipitation, and achieving good results. It has good feasibility and broad prospects.

[0055] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0056] Example 1 This embodiment provides a method for preparing a titanium oxycarbide electrode, comprising the following steps: Step S1: 30 g of graphite powder and 100 g of titanium dioxide are mixed in a three-dimensional mixer for 30 min, 16 g of water is added as a binder, and the mixture is formed in a mold with a diameter of 20 mm at a pressure of 300 MPa. After demolding, the mixture is dried in an oven at 105°C for more than 12 h. The above-mentioned blank is thermally reduced at 1380°C in a vacuum furnace for 5 h, with a heating rate of 10°C / min. After cooling out of the furnace, the reduction product is crushed to less than 840 μm for standby use.

[0057] Step S2: Take 33.4 g of asphalt (particle size 2000 μm) with a fixed carbon content of 39.0% and add it to the above-mentioned crushed reduction product, add 7 g of 2% polyvinyl alcohol solution as a binder, mix well and mold it in a mold with a diameter of 20 mm at a pressure of 80 MPa, and dry it in an oven at 100°C for more than 12 h after demolding. The resulting blank is sintered in an atmosphere furnace by passing Ar gas, with a heating rate of 10°C / min, and kept at 350°C, 500°C, and 950°C for 1 h, respectively, and cooled out of the furnace to obtain a density of 1.8 g / cm 3 of titanium oxycarbide electrode.

[0058] Using this electrode as the anode, electrolysis was carried out in an equimolar NaCl-KCl molten salt system. After the electrolysis was completed, the anode shape remained intact and the anode dissolution rate reached 99%.

[0059] Example 2 This embodiment provides a method for preparing a titanium oxycarbide electrode, comprising the following steps: Step S1: 27 g of graphite powder and 100 g of titanium dioxide were mixed in a three-dimensional mixer for 30 min, 15 g of water was added as a binder, and the mixture was molded in a mold with a diameter of 20 mm at a pressure of 200 MPa. After demolding, the mixture was dried in an oven at 105°C for more than 12 h. The above-mentioned blank was thermally reduced at 1480°C in a vacuum furnace for 4 h, with a heating rate of 10°C / min. After cooling out of the furnace, the reduced product was crushed to less than 420 μm for standby use.

[0060] Step S2: Take 28 g of asphalt (particle size 1000 μm) with a fixed carbon content of 51.0% and add it to the above-mentioned crushed reduction product, add 7 g of 2% polyvinyl alcohol solution as a binder, mix well, and mold it in a mold with a diameter of 20 mm at a pressure of 60 MPa. After demolding, dry it in an oven at 100°C for more than 12 h. The resulting blank is sintered in an atmosphere furnace by passing Ar gas, with a heating rate of 10°C / min, and kept at 350°C, 500°C, and 950°C for 1 h, respectively, and cooled out of the furnace to obtain a density of 2.1 g / cm 3 of titanium oxycarbide electrode.

[0061] With this electrode as anode, in NaCl-KCl-1.0%TiCl n (2<n<3) Electrolysis in the molten salt system. After the electrolysis is completed, the anode shape remains intact and the anode dissolution rate reaches 92%.

[0062] Example 3 This embodiment provides a method for preparing a titanium oxycarbide electrode, comprising the following steps: Step S1: 23 g of graphite powder and 100 g of titanium dioxide are mixed in a three-dimensional mixer for 30 min, 15 g of water is added as a binder, and the mixture is formed in a mold with a diameter of 20 mm at a pressure of 200 MPa. After demolding, the mixture is dried in an oven at 105°C for more than 12 h. The above-mentioned blank is thermally reduced at 1550°C in a vacuum furnace for 4 h, with a heating rate of 10°C / min. After cooling out of the furnace, the reduction product is crushed to less than 420 μm for standby use.

[0063] Step S2: Take 19g of asphalt (particle size 1000 μm) with a fixed carbon content of 59.0% and add it to the above-mentioned crushed reduction product, add 7g of 2% polyvinyl alcohol solution as a binder, mix well and mold it in a mold with a diameter of 20 mm at a pressure of 20 MPa, and dry it in an oven at 100°C for more than 12 hours after demoulding. The resulting blank is sintered in an atmosphere furnace by passing Ar gas, with a heating rate of 10°C / min, and kept at 350°C, 500°C, and 950°C for 1 hour respectively, and then cooled out of the furnace to obtain a density of 1.5 g / cm 3 of titanium oxycarbide electrode.

[0064] With this electrode as anode, in NaCl-KCl-2.0%TiCl n (2<n<3) Electrolysis in the molten salt system. After the electrolysis is completed, the anode shape remains intact and the anode dissolution rate reaches 91%.

[0065] Comparative Example 1 The difference from Example 3 is that the step of adding asphalt in step S2 is not included, and the details are as follows: Step S1: 23 g of graphite powder and 100 g of titanium dioxide were mixed in a three-dimensional mixer for 30 min, 15 g of water was added as a binder, and the mixture was formed in a mold with a diameter of 20 mm at a pressure of 200 MPa. After demolding, the mixture was dried in an oven at 105°C for more than 12 h. The above-mentioned blank was thermally reduced at 1550°C in a vacuum furnace for 4 h, with a heating rate of 10°C / min. After cooling out of the furnace, the reduced product was crushed to less than 420 μm for standby use.

[0066] Step S2: Add 5.5 g of 2% polyvinyl alcohol solution as a binder, mold in a mold with a diameter of 20 mm at a pressure of 20 MPa, and dry in an oven at 100°C for more than 12 h after demolding. Sinter the resulting blank in an atmosphere furnace with Ar gas, heating rate of 10°C / min, constant temperature at 1200°C for 1 h, and after cooling out of the furnace, obtain a density of 2.0 g / cm 3 of titanium oxycarbide electrode.

[0067] With this electrode as anode, in NaCl-KCl-2.0%TiCl n (2<n<3) Electrolysis in a molten salt system. During the electrolysis process, due to the flushing of the anode gas (CO), a large amount of anode material is scattered to the bottom of the molten salt, and the electrolysis cannot be continued.

[0068] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a titanium oxycarbide electrode, characterized in that: The following steps are involved: S1: mixing a carbon reducing agent, a titanium-containing material and a binder, and then performing a carbon thermal reduction treatment to obtain a reduction product; S2: The reduction product is mixed with asphalt and a binder, and then sintered to obtain a titanium oxycarbide electrode.

2. The preparation method according to claim 1, characterized in that: The fixed carbon content of the asphalt is 5 to 95 wt%; The particle size of the asphalt is 40-5000 μm.

3. The preparation method according to claim 1 or 2, characterized in that: The carbon reducing agent is selected from any one or more of graphite, petroleum coke or amorphous carbon; The titanium-containing material is selected from any one or more of titanium dioxide, rutile, artificial rutile, titanium concentrate, titanium slag or high-titanium slag; The binder in steps S1 and S2 is independently selected from water and / or an aqueous solution of polyvinyl alcohol; The mass fraction of polyvinyl alcohol in the aqueous solution of polyvinyl alcohol is 1-2%.

4. The preparation method according to any one of claims 1 to 3, characterized in that The molar ratio of carbon in the carbon reducing agent to titanium dioxide in the titanium-containing material is 1.6:1 to 2.4:1; The water content of the mixture of the carbon reducing agent, the titanium-containing material and the binder is 12-15%.

5. The preparation method according to any one of claims 1 to 4, characterized in that The mass of the asphalt accounts for 10-30% of the total mass of the asphalt and the titanium oxycarbide electrode; The mass of the binder in step S2 accounts for 5-7% of the total mass of the reduction product and asphalt.

6. The preparation method according to any one of claims 1 to 5, characterized in that The carbon thermal reduction treatment is performed at a temperature of 1280-1800°C, a time of 0.5-10 h, and a pressure of ≤1 atm; The heating rate in the carbon thermal reduction treatment is 5-15 °C / min; The carbon thermal reduction treatment is performed in an inert atmosphere or a vacuum environment.

7. The preparation method according to any one of claims 1 to 6, characterized in that The sintering is carried out in an inert atmosphere and is carried out according to the following procedure: Raise the temperature to 300-400°C at a rate of 5-15°C / min and keep at this temperature for 1-5 h; Raise the temperature to 450-550°C at a rate of 5-15°C / min and keep at this temperature for 1-5 h; Raise the temperature to 850~1050℃ at a rate of 5~15℃ / min and keep it at this temperature for 1~5 h.

8. The preparation method according to any one of claims 1 to 7, characterized in that After the mixing in step S1, compression molding is performed, and then carbon thermal reduction treatment is performed; the compression molding pressure is 25-600 MPa; Step S2: the reduction product is crushed and sieved in advance, and the mesh number of the sieve is 20-100 mesh; After the mixing in step S2, compression molding is performed, and then sintering is performed; the compression molding pressure is 5~80MPa.

9. The titanium oxycarbide electrode prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The density of the titanium oxycarbide electrode is 1.5 g / cm 3 above.

10. Use of the titanium oxycarbide electrode according to claim 9 in titanium extraction by molten salt electrolysis.

Citation Information

Patent Citations

  • Pure titanium production from titanium monoxide / titanium carbide soluble solid anode electrolysis

    CN1712571A